The utilization of decellularized tendon slices to provide an inductive microenvironment for the proliferation and tenogenic differentiation of stem cells. (June 2015) - Ning, Liang-Ju; Zhang, Ya-Jing; Zhang, Yi; Qing, Quan; Jiang, Yan-Lin; Yang, Jie-Liang; Luo, Jing-Cong; Qin, Ting-Wu
Abstract: The extracellular matrix (ECM) microenvironment for the stem cell niches, including but not limited to the biochemical composition, matrix topography, and stiffness, is crucial to stem cell proliferation and differentiation. The purpose of this study was to explore the capacity of the decellularized tendon slices (DTSs) to induce stem cell proliferation and tenogenic differentiation. Rat adult stem cells, including tendon-derived stem cells (TDSCs) and bone marrow-derived stem cells (BMSCs), were identified to have universal stem cell characteristics. The DTSs were found to retain the native tendon ECM microenvironment cues, including the inherent surface topography, well-preserved tendon ECM biochemical composition and similar stiffness to native tendon. When the TDSCs and BMSCs were cultured on the DTSs respectively, the LIVE/DEAD assay, alamarBlue ® assay, scanning electron microscopy examination and qRT-PCR analysis demonstrated that the DTSs have the capacity to support these stem cells homogeneous distribution, alignment, significant proliferation and tenogenic differentiation. Taken together, the findings of this study indicate that the DTSs can provide a naturally inductive microenvironment for the proliferation and tenogenic differentiation of TDSCs and BMSCs, supporting the use of decellularized tendon ECM as a promising and valuable approach for tendon repair/reconstruction.